Direct solid-state nucleation and charge-transport dynamics of alkali metal-intercalated M2Mo6S6 (M = K, Rb, Cs) nanorods. Issue 31 (10th June 2020) - Perryman, Joseph T.; Kulkarni, Ambarish R.; Velázquez, Jesús M.
Abstract : Microwave-assisted solid-state heating has been employed to induce anisotropic nucleation of M2 Mo6 S6 (M = K, Rb, Cs) nanorods without a template for the first time, and interfacial charge-transport properties of these rods are evaluated. Abstract : Microwave-assisted solid-state heating has been employed to control anisotropic growth of M2 Mo6 S6 (M = K, Rb, Cs) pseudo-Chevrel phase nanorods without a growth template for the first time. Pronounced preferential crystal nucleation along the hexagonal axis is observed, and electrochemical methods are implemented to elucidate viability for employment of these materials in energy storage and energy conversion systems. It is observed that these nanomaterials exhibit moderate and under-explored capacitive behavior with charge storage capabilities ranging from 2–8 F g −1 in strongly acidic aqueous electrolyte, as well as promising electrochemical performance, evolving hydrogen gas at 10 mA cm −2 under an applied bias of less than 300 mV vs. RHE.